Digital Marketing Strategies for Agricultural Products in Enhancing Farmer Competitiveness: A Literature Review - Mikhael Jibrael Balo; Sanny Feria Juliana; Feliks Arfid Guampe (CV. ALIM'SPUBLISHING, 2026)
Digital marketing has become a strategic instrument for strengthening the competitiveness of farmers, yet empirical evidence remains fragmented across contexts, commodities, and methods. This study aims to synthesize the literature on digital marketing strategies for agricultural products and their contribution to farmers’ competitiveness. A systematic literature review was conducted following the PRISMA 2020 protocol. Searches in Google Scholar, GARUDA/SINTA, Scopus, and DOAJ identified 749 records published in 2017–2025; after duplicate removal, screening, and full-text eligibility assessment, 25 articles were included. Thematic analysis produced five themes: (1) digital marketing strategies and the competitiveness of agricultural products; (2) e-commerce and agricultural marketplaces; (3) social media as a marketing channel; (4) digital literacy and farmer capability; and (5) the impact of digitalization on market access, income, and value chains. The review shows that digital marketing enhances competitiveness through four mechanisms: transaction-cost efficiency, market expansion, product value-added and branding, and improved bargaining position through price information. However, these benefits are conditional on digital literacy, infrastructure, and institutional support. The findings imply that interventions should integrate capacity-building, mentoring, and enabling policies rather than focusing solely on technology adoption.